2020
DOI: 10.1007/s00415-020-10113-0
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of death certificates for recording parkinsonian syndromes and associated dementia

Abstract: Introduction: Death certification is often used to identify patients with certain diseases in epidemiologic research. There have been few studies looking at the accuracy of recording of parkinsonian diagnoses, any associated dementia and the cause of death on death certificates in people with parkinsonian conditions. This study aimed to assess this.Methods: Data for these analyses were derived from a prospective incident cohort of degenerative/vascular parkinsonian syndromes with lifelong follow-up from Scotla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Nonetheless, there are limits inherent to the accuracy of mortality records. In the Veneto Region between 2008 and 2015, PD was mentioned in only 60% of death certificates of patients with a previous diagnosis of PD [ 5 ]; such sensitivity is within the range reported from older reports and recent UK studies: 53% in North Wales [ 11 ], and 68% in Scotland [ 12 ].…”
Section: Discussionmentioning
confidence: 72%
“…Nonetheless, there are limits inherent to the accuracy of mortality records. In the Veneto Region between 2008 and 2015, PD was mentioned in only 60% of death certificates of patients with a previous diagnosis of PD [ 5 ]; such sensitivity is within the range reported from older reports and recent UK studies: 53% in North Wales [ 11 ], and 68% in Scotland [ 12 ].…”
Section: Discussionmentioning
confidence: 72%
“…Mortality data using only population‐based death records have often been used to estimate the epidemiology of PD. However, this approach is problematic due to inaccuracies in death certificate data 8–11 . Naturally, this also concerns the death certificate data at our disposal.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies suggested that the improved accuracy of registration practices might affect the results of death certificates and lead to a steady increase in PD mortality ( 14 ). This could also partially explain the significant differences between countries according to the HDI.…”
Section: Discussionmentioning
confidence: 99%